PATRON CLIENT: KONTRAK SEMI MUDHARABAH DALAM TEORI KEAGENAN DI PERIKANAN LAUT - Qurrata, Vika Annisa (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2017)
This study aims to find out how the skipper (as principal) interact with pandega fishermen (as agents) in creating mudaraba-style contracts in marine fisheries (patron-client). With in-depth interviews, there are two important findings: in general juragandi Blue Water Waters especially in the payang fishermen and the lifeboats impose exploitation fees or operational costs to the pandega fishermen in a shared way. Then there is a bit of aberration in the profit-sharing system, but this institution seems to exist and be a deal that never openly conflicts. Based on the findings and some literature, mudaraba contracts can be a purely alternative financing if it is more just and beneficial to both parties ie the master / shahibul maal as principal and pandega / mudharib as agent. To minimize the possibility of moral hazard and adverse selection on the mudaraba contract, it is advisable to monitor each return of the vessel for the sale of fish and the skipper can place one of the trustees other than the pandega fisherman.